PENGGUNAAN GAME ONLINE DENGAN GANGGUAN MENTAL EMOSIONAL PADA REMAJA - mariyati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
Excessive use of online games has an impact on adolescent mental health. The use of online games has an impact on physical and mental health. Especially in mental health, adolescents experience thought disorders, anxiety, behavioral disorders such as irritability, anti-social and depression. Teenagers in Tambakharjo Village have a habit of playing online games such as Mobile Legend and Free Fire. Complaints felt by adolescents are not concentrating on studying and working, irritability, lack of sleep and anxiety if they lose at play. The purpose of this study was to analyze the relationship between the use of online games and emotional mental disorders in adolescents in Tambakharjo Village, Semarang City.The number of samples in this study were 35 which met the inclusion criteria. The type of research used in this research is cross-sectional quantitative method which aims to analyze the relationship between the two independent variables and the dependent variable. The research instrument used was a questionnaire on the use of online games and emotional mental disorders which had been valid and reliable by previous researchers. The bivariate analysis test used was rank spearmen.The characteristics of the respondents in this study were the majority of men 65.7%, middle adolescent age (14-16) 45.7%, and status as a student 77.1%. The use of online games includes a frequent rate of 48.6%, the majority of mental health have emotional mental disorders of 60%. Spearmen's rank test showed a p-value of 0.00 (<0.05) with an rho of 0.607. There is a relationship between the use of online games and adolescent mental health in the Tambakharjo Village.